Existence result for hemivariational inequality involving p(x)-Laplacian - Barnaś, Sylwia (My University, 2012)
In this paper we study the nonlinear elliptic problem with $p(x)$-Laplacian (hemivariational inequality). We prove the existence of a nontrivial solution. Our approach is based on critical point theory for locally Lipschitz functionals due to Chang [J. Math. Anal. Appl. 80 (1981), 102-129].
Opuscula Mathematica
Keywords: p(x)-Laplacian; Palais-Smale condition; mountain pass theorem; variable exponent Sobolev space